Estudo sócio-epidemiológico das criações de ovinos e caprinos participantes de exposições agropecuárias do Rio Grande do Norte - Fernandes, Leíse Gomes (Universidade Federal Rural do Semi-Árido, 2011)
The objective of this study was to describe characteristics of systems creations of goats and sheep farming exhibitions of participants, and to study the occurrence of Brucella ovis infections in sheep and lentivirus, and leptospirosis caseous lymphadenitis in goats and sheep and their risk factors. Carried out 64 questionnaires, examined 327 sera from 246 goats and sheep. The worms, foot pad dermatitis and lymphadenitis were more health problems reported by producers. The sanitary practices adopted, in general, are little used in the properties of goats and sheep. The semi-intensive system (67.7%) is the most used and 71% of producers buy animals from other places. The frequency of seropositive sheep B. ovis was 28% accounting for 71.9% of farms with sheep positive for B. ovis in the study. 25% of farms surveyed had one or more seropositive goats and sheep lentiviruses. Of the 138 animals tested positive for leptospirosis serovar Autumnalis was the most frequent, being found in 76.19% 38.88% in goats and sheep. In the study of case-control analysis of risk factors, herd size and purchase of animals showed a strong association. The caseous lymphadenitis has a high incidence in herds serological (92.2%). It can be concluded that the animals are seropositive for exposure to infectious diseases and inadequate management observed in most producers can spread the disease spread and put other animals at risk.
Socio-epidemiological study of the creations of sheep and goats participants of agricultural exhibition of Rio Grande do Norte
Keywords: epidemiology; brucellosis in sheep; CAE; Maedi-Visna; leptospirosis; caseous lymphadenitis; epidemiologia; brucelose ovina; CAE; Maedi-Visna; leptospirose; linfadenite caseosa; CIENCIAS AGRARIAS::MEDICINA VETERINARIA